From Analytical to Computational: Revisiting Subsidence Prediction with New Tools - Saavedra-Rosas, Jose; Jarosz, Andrew (KGHM CUPRUM Ltd. R&D Centre, 2012)
According to an old saying "when all you have is a hammer, every problem looks like a nail". In many cases this maxim applies to our research, analytical activities and abilities to model and solve real case studies. The current speed of technological developments makes sooner or later our toolboxes, developed and built in the past, obsolete. This motivates and validates the question whether it is reasonable to revisit some old problems and assess the quality of the solutions we have available for them now. In particular, authors use an example, relating to prediction (calculation) of mine subsidence, to illustrate how this problem can be revisited and solution methods updated using new computational techniques.